PENGARUH EARNINGS AFTER TAX, CURRENT RATIO, DEBT TO EQUITY RATIO TERHADAP DEVIDEN PAYOUT RATIO - Sarmo, Sulaeman; Muttaqillah, Muttaqillah; Effendi, Handri Amin (Sekolah Tinggi Ilmu Ekonomi AMM Mataram, 2019)
This research was conducted to determine the effect of current ratio, earnings after taxes, debt to equity ratio on dividend payout ratio, to real estate companies in 2015-2017. The sampling technique used purposive sampling with a sample size of 41 companies. The hypothesis testing method used was logistic regression analysis by using the classical assumption of multicollinearity. The results show that earnings after taxes affect the dividend of the payout ratio, while the current ratio and debt to equity ratio do not affect the dividend payout ratio